PENGARUH KECERDASAN INTELEKTUAL TERHADAP PEMAHAMAN AKUNTANSI : KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERATING - Agus Agus; Kirmizi Kirmizi; Enni Savitri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This research purpose to test the influence of intellectual intelligence against the understanding of accounting with spiritual intelligence and emotional intelligence as a variable moderation. Population and sample in the research master's degree Accounting students, this University of Riau. This research got 101 sample respondents. By using regression analysis models with spss version 16. The results showed that the intelligence of the intellectual influence on the understanding of accounting. intellectual intelligence to accounting understanding moderated with spiritual intelligence. intellectual intelligence does not affect accounting understanding moderated by emotional intelligence.